2020
DOI: 10.1093/occmed/kqaa111
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported alcohol consumption in doctors

Abstract: Background The UK government has prioritized reducing the harmful effects of excessive alcohol consumption on mental and physical well-being. Aims To assess self-reported alcohol consumption amongst doctors at an acute London Trust. Methods An opportunistic, anonymous, survey was conducted by Postgraduate Education Fellows over 2 weeks in December 2018. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…64 This study also reported that of the 383 physicians who reported risky substance misuse (alcohol or other drugs, or both), 76·9% felt their substance misuse was unproblematic. A smaller UK-based study reported that 22 (20%) of 109 doctors drank alcohol nearly exceeding, or exceeding, recommended levels, 65 although only 5% of doctors from another study met the criteria for alcohol dependence. 66 These results suggest that, compared with the general population, physicians might consume alcohol at a similar rate, or perhaps at a higher rate.…”
Section: Substance Misuse Among Physiciansmentioning
confidence: 98%
“…64 This study also reported that of the 383 physicians who reported risky substance misuse (alcohol or other drugs, or both), 76·9% felt their substance misuse was unproblematic. A smaller UK-based study reported that 22 (20%) of 109 doctors drank alcohol nearly exceeding, or exceeding, recommended levels, 65 although only 5% of doctors from another study met the criteria for alcohol dependence. 66 These results suggest that, compared with the general population, physicians might consume alcohol at a similar rate, or perhaps at a higher rate.…”
Section: Substance Misuse Among Physiciansmentioning
confidence: 98%
“…According to self-assessment of alcohol consumption by emergency physicians in the UK, only 14% were abstaining from alcohol. 21% drank once a month or less, 31% − 2 to 4 times a month, 25% − 2 to 3 times a week and 9% -more than 4 times a week (Savage et al 2020). It was revealed that the healthcare practitioners were more prone to emotional burnout due to emotional interactions with their patients on a daily basis (Singh et al 2017).…”
Section: Discussionmentioning
confidence: 99%